Characteristic Features of Financial Statements of Sports Clubs with the Example of the Polish Basketball League - Obrzeżgiewicz, Dawid (Studia Oeconomica Posnaniensia, 2019)
The purpose of the article is to identify the characteristics of the financial reports of sports clubs of the Polish Basketball League. The research subject is an analysis of the financial reports of sports clubs in Poland in terms of financial and sport goals. The research subjects are sports clubs competing in the Polish Basketball League. The analysis period covers the years 2016-2017 covering the 2016/2017 season and the 2017/2018 season. The article has three parts. The first part describes the specificity of sports club activities and their impact on financial statements. The second section is devoted to an analysis of the balance sheets of sports clubs. In the third part, income statements were analysed in terms of achieving the financial and sports goals of the sports clubs. The article draws attention to the problem of negative equity in most clubs in the Polish Basketball League.